Niveles séricos de colesterol total, colesterol hdl e índice aterogénico en personas adultas de ambos sexos de los clubes de madres del sector II del distrito de Florencia de Mora – marzo 2009” - Moncada Wuton, Eduardo Junior (2009)
This research work deals with the determinations of total serum cholesterol, HDL cholesterol and atherogenic index in adults of both sexes in Mothers Clubs of District Sector II Florencia de Mora. To accomplish this work was carried out data collection which lasted twenty days, which was conducted in search of the target population, relevant surveys, the sampling and biochemical determinations for, then became the analysis of results , resulting in: Total Cholesterol Desirable 76%, of which 67% and 9% are female and male respectively; Moderately High Total Cholesterol 18%, of which 17% and 1% are female and male respectively and Elevated Total Cholesterol 6%, of which 5% and 1% are female and male respectively. We also collected results: High Risk HDL Cholesterol 53%, of which 45% and 8% are female and male respectively, Desirable HDL Cholesterol 44%, of which 42% and 2% are females and male respectively, and HDL Cholesterol Protective 3%, of which 2% and% are female and male respectively. Finally the results were obtained: Atherogenic Index with normal 46%, of which 42% and 4% are female and male respectively Atherogenic Index with coronary risk 54%, of which 47% and 7% correspond to female and male